Makna dan Peran Eufemisme dalam Opini Surat Kabar Kompas Edisi 1-31 Oktober 2019 - Ika Apriliani, Reti (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This study highlights the use of euphemism in the context of mass media, particularly in newspapers, providing a significant contribution to understanding this phenomenon. Although previously noted, this research delves deeper into how euphemisms are employed by the media to manage sensitivity and responsibility in conveying information to the public. It also reveals the impact of euphemistic language on the understanding and interpretation of media messages, highlighting aspects that have not been fully explored before. Furthermore, this study offers a fresh perspective on the dynamics of communication in the context of mass media, especially in language development and accurate information dissemination. By examining the use of euphemism in newspapers, this research opens a new window into understanding the language strategies employed by media outlets to achieve communicative goals. Adopting a qualitative approach and descriptive method allows the author to describe, analyze, and draw conclusions from the data accurately. Documentation and hermeneutic techniques are employed in data collection to obtain a thorough and in-depth understanding. The analysis results reveal several patterns in the use of euphemism, such as borrowing words from foreign languages, using circumlocution, and avoiding harsh language. As a suggestion, future research should pay more attention to references and data collection, as well as consider more systematic methods in data processing. Thus, this study is expected to make a significant contribution to understanding the use of euphemism in mass media and public communication.